Influence of polymer structure and amount on microstructure and properties of polyethylene-modified asphalt binders - K. Lakshmi Roja (14159028) (2022)
In recent years, the use of polyethylene (PE) for asphalt modification has been gaining increased attention due to the environmental sustainability and cost-saving benefits. To optimize the performance of the PE-asphalt blends, it is necessary to understand the polymer-binder interactions and their impact on the properties of the modified asphalt binder. In this study, low-density polyethylene (LDPE) with low and high melt flow index (MFI), i.e., LDPE4 and LDPE70, were blended with Pen 60-70 asphalt binder in dosages ranging from 1 to 5 wt.%. PE Wax was also added to the binder or the PE-binder blend to enhance dispersion. The dispersion of PE in the binder and the phase stability of the modified binder were investigated by optical microscope. The equivalent diameter of PE domains increased with time and the polymer dosage level. The addition of PE wax improved the polymer dispersity in the LDPE4 blends. The polymer dispersity in LDPE70 blends was good without adding PE Wax, attributed to the higher MFI value (low molecular weight) of LDPE70. In addition, to understand the stability of polymer modified binder, the steady shear viscosity-temperature profile of these binders was studied using a rotational viscometer. The dynamic rheological properties and performance of the PE-binder blends were evaluated using the dynamic shear rheometer. Based on the microstructure, all other rheological and performance properties, it was concluded that the 3% LDPE70 binder has better polymer dispersity, better low and high temperature performance characteristics. Other Information Published in: Materials and Structures License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1617/s11527-021-01683-0